Penggunaan Media Pembelajaran Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Pelajaran IPA Kelas Lv SD N 2 Krakitan Bayat - Lestari, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to improve the learning process to improve social studies learning outcomes through the media of learning map images. This classroom action research was designed in two cycles. The subjects of this research were class IV students at SDN 2 Krakitan for the 2022/2023 academic year with a total of 14 students. The object of this research is improving social studies learning outcomes. The results of this research show that there has been an increase in social studies learning outcomes by 16.00%. It is hoped that colleagues will try to carry out PTK in order to improve learning. In learning in elementary schools, especially social studies, authorized agencies such as the District Education Office and other agencies are expected to be able to use the results of this research in the context of developing social studies learning in elementary schools using map drawing media.